Scientific retraction: a synonym for pseudoscience? - Sheth, Bhavisha P.; Thaker, Vrinda S. (Acta Bioethica, 2014)
The phenomenon of scientific retraction is a shameful act for the scientific community, but a necessity to maintain the purity of science. The two main causes for retractions include plagiarism and research misconduct. The post retraction citation of articles is again a repetition of inappropriateness. Hence the editorial, peer review policies should be revised and the retractions should be publicized more to avoid the citation of the invalid literature. Also, the scientific readership has a responsibility to evaluate the scientific validity of published studies.